Elemental diet therapy for eosinophilic gastroenteritis and dietary habits. Issue 1 (12th March 2022) - Higuchi, Tsukasa; Tokunaga, Mai; Murai, Takemi; Takeuchi, Kouichi; Nakayama, Yoshiko
Abstract: Background: Eosinophilic gastrointestinal disorders (EGID) are a group of conditions with increased eosinophilic infiltration in any part of the gastrointestinal tract. Although an allergic reaction to certain foods is considered the main cause of EGID, their detailed pathomechanism has not yet been elucidated, nor have proper management strategies been fully established. Moreover, some patients with intractable EGID are resistant to such therapies as an empirical elimination diet and corticosteroids. Methods: We analyzed retrospectively the medical records of four children with intractable eosinophilic gastroenteritis (EGE) managed with elemental diet therapy (EDT) using an amino acid‐based formula. Results: All patients displayed resolution of their symptoms after 2 weeks of EDT. Three patients successfully completed food reintroduction and could return to their normal life. No adverse events related to EDT were recorded. Conclusions: Elemental diet therapy appears effective and safe for treating pediatric intractable EGE symptoms. Afterwards, the patient's dietary habits should be considered during carefully monitored food reintroduction. With the relatively small number of published case reports and no randomized trials, more study is needed on EDT for EGE.